Relationship Online Game Addiction with Interpersonal Communication and Social Interaction in Adolescents - Yusuf, Ah; Krisnana, Ilya; Ibrahim, Achmad (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2019)
Introduction: Online games have a big influence on users. Users of online games tend to experience addiction in the game they like, marked by playing> 4-5 hours per day, always thinking of online games even if they don't play games, and always prioritize playing online games rather than other activities. The purpose of this study was to determine the relationship of online game addiction with interpersonal communication and social interaction in adolescents.Method: Research design with Cross-Sectional approach. The total sample is 210 respondents. The sampling technique uses simple random sampling. Data were analyzed using spearman rho's analysis with a significance level of p <0.05.Results: The results showed that the one associated with online game addiction was interpersonal communication (p = 0.027 and r = - 0.152), and social interaction (p = 0,000 and r = 0.248).Conclusion: Online game addiction has a relationship with interpersonal communication, the higher the online game addiction, the lower the interpersonal communication produced. Addiction to online games has a relationship with social interaction, the higher the addiction to online games, the lower the social interaction produced.